The histone deacetylase inhibitor chidamide induces intermittent viraemia in HIV‐infected patients on suppressive antiretroviral therapy. Issue 11 (25th December 2020) - Li, JH; Ma, J; Kang, W; Wang, CF; Bai, F; Zhao, K; Yao, N; Liu, Q; Dang, BL; Wang, BW; Wei, QQ; Kang, WZ; et al.
Abstract : Objectives: To evaluate the safety and efficacy of chidamide to reverse HIV‐1 latency in vivo and to compare the effects of four clinically tested histone deacetylase (HDAC) inhibitors on non‐histone proteins in vitro . Methods: Participants received chidamide orally at 10 mg twice weekly for 4 weeks while maintaining baseline antiretroviral therapy. The primary outcome was plasma viral rebound during chidamide dosing and the secondary outcomes were safety, pharmacokinetic and pharmacodynamic profiles, changes in cell‐associated HIV‐1 RNA and HIV‐1 DNA, and immune parameters. Western blotting was used to compare the in vitro effects of the four HDAC inhibitors on HSP90, NF‐κB and AP‐1. Results: Seven aviraemic participants completed eight oral doses of chidamide, and only grade 1 adverse events were observed. Cyclic increases in histone acetylation were also detected. All participants showed robust and repeated plasma viral rebound (peak viraemia 147–3850 copies/mL), as well as increased cell‐associated HIV‐1 RNA, during chidamide treatment. Furthermore, we identified an enhanced HIV‐1‐specific cellular immune response and a modest 37.7% (95% CI: 12.7–62.8%, P  = 0.028) reduction in cell‐associated HIV‐1 DNA. Compared with the other three HDAC inhibitors, chidamide had minimal cytotoxicity in vitro at clinically relevant concentrations and showed mechanistically superior effects on non‐histone proteins, including HSP90, NF‐κB and AP‐1. Conclusions: Chidamide safely and vigorously disrupts HIV‐1 latency in vivo, which makes it a promising latency‐reversing agent.